Sandwich type plasmonic platform for MEF using silver fractals. Issue 42 (9th October 2015) - Raut, Sangram L.; Rich, Ryan; Shtoyko, Tanya; Bora, Ilkay; Laursen, Bo W.; Sørensen, Thomas Just; Borejdo, Julian; Gryczynski, Zygmunt; Gryczynski, Ignacy
Abstract : In this report, we describe a plasmonic platform with silver fractals for metal enhanced fluorescence (MEF) measurements. Abstract : In this report, we describe a plasmonic platform with silver fractals for metal enhanced fluorescence (MEF) measurements. When a dye containing surface was brought into contact with silver fractals, a significantly enhanced fluorescence signal from the dye was observed. Fluorescence enhancement was studied with the N -methyl-azadioxatriangulenium chloride salt (Me-ADOTA·Cl) in PVA films made from 0.2% PVA (w/v) solution spin-coated on a clean glass coverslip. The Plasmonic Platforms (PP) were assembled by pressing together silver fractals on one glass slide and a separate glass coverslip spin-coated with a uniform Me-ADOTA·Cl in PVA film. In addition, we also tested ADOTA labeled human serum albumin (HSA) deposited on a glass slide for potential PP bioassay applications. Using the new PP, we could achieve more than a 20-fold fluorescence enhancement (bright spots) accompanied by a decrease in the fluorescence lifetime. The experimental results were used to calculate the extinction (excitation) enhancement factor ( G A ) and fluorescence radiative rate enhancements factor ( G F ). No change in emission spectrum was observed for a dye with or without contact with fractals. Our studies indicate that this type of PP can be a convenient approach for constructing assays utilizing metal enhanced fluorescence (MEF) without the need for depositing the material directly on metal structures platforms.